2017
DOI: 10.1063/1.4993974
|View full text |Cite
|
Sign up to set email alerts
|

Controlling of magnetocaloric effect in Gd2O3@SiO2 nanocomposites by substrate dimensionality and particles’ concentration

Abstract: The magnetocaloric effect (MCE) of hybrid nanostructures consisting of fine gadolinium oxide (Gd2O3) nanoparticles with diameter 7 nm and 12 nm loaded into the pores of the periodically ordered mesoporous silica with hexagonal (SBA-15) or cubic (SBA-16) symmetry were investigated. The concentration effect of the added nanoparticles (NPs) and the effect of the silica matrix dimensionality on the structural properties, magnetization M(H), magnetic entropy change ΔSM, and parameters A(T) and B(T) derived from Arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Figure 1 a shows SANS data obtained for the SBA15/Gd 2 O 3 -0.01 M composite. The system is characteristic of very low nanoparticle concentration what has been evidenced by a number of experimental methods (HRTEM, HE-XRD, nitrogen adsorption/desorption volumetry, magnetic measurements) previously 16 , 18 . The matrix pores are therefore deemed sparsely occupied by the Gd 2 O 3 NPs and the scattering signal from the composite is supposed to closely resemble that of the hollow SBA15 matrix.…”
Section: Resultsmentioning
confidence: 91%
“…Figure 1 a shows SANS data obtained for the SBA15/Gd 2 O 3 -0.01 M composite. The system is characteristic of very low nanoparticle concentration what has been evidenced by a number of experimental methods (HRTEM, HE-XRD, nitrogen adsorption/desorption volumetry, magnetic measurements) previously 16 , 18 . The matrix pores are therefore deemed sparsely occupied by the Gd 2 O 3 NPs and the scattering signal from the composite is supposed to closely resemble that of the hollow SBA15 matrix.…”
Section: Resultsmentioning
confidence: 91%
“…Figure 1a shows SANS data obtained for the SBA15/Gd 2 O 3 -0.01M composite. The system is characteristic of very low nanoparticle concentration what has been evidenced by a number of experimental methods (HRTEM, HE-XRD, nitrogen adsorption/desorption volumetry, magnetic measurements) previously 11,13 . The matrix pores are therefore deemed sparsely occupied by the Gd 2 O 3 NPs and the scattering signal from the composite is supposed to closely resemble that of the hollow SBA15 matrix.…”
Section: Resultsmentioning
confidence: 92%
“…Although the employed scaling analysis has been established for bulk materials, we demonstrate its rst valid application to the nanocomposite systems. The results presented in this work are set into the context of our profound experimental and theoretical analysis that we have carried out to the systems of this kind in recent years [11][12][13][14][15][16][17] . Altogether they provide a comprehensive insight into the nature and performance of advanced nanocomposites that we have prepared and examined.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies, where series of related systems have been analyzed and compared, revealed the influence of NPs concentration and silica dimensionality on adsorption/desorption capacity or magnetic characteristics of the composites in general 14 . Further, it has been demonstrated that size of NPs embedded in pores controls the magnitude of magnetocaloric effect 15 . It turned out that despite of the same wet-impregnation method employed during the particular matrix modification, several scenarios of nanoparticle formations are possible.…”
Section: Introductionmentioning
confidence: 99%